Does Parental Work from Home Influence Development of Sleep Bruxism in Children - GURUNATHAN, DEEPA; MS, NIVEDHITHA; MOSES, JOYSON; MATHEW, MEBIN GEORGE; RAMAKRISHNAN, MAHESH (The journal of contemporary issues in business and government, 2020)
Bruxism is a disorder characterized by grinding and clenching of teeth which may be due to various etiological factors. Though various etiological factors have been associated, the exact cause is known. Stress has been positively associated with bruxism. The prevalence of bruxism is seen to be high in children and reduces with age. The lockdown imposed due to COVID-19 has been stressful for children and parents with the introduction of work from home for parents. This study was initiated to find if work from home is a stress factor for children with bruxism. An online survey link was shared to 156 parents of 6–8-year-old children who visited the department of pedodontics and preventive dentistry. 111 parents responded to the survey. 71.2% of the parents found their children to be stressed of which 30.4% believed online classes and the lack of parental interaction due to work from home caused stress. 71.2% of the parents believed that consultation was necessary despite of lockdown. Within the limits of the study it has been found that work from home can be considered as a stress factor for children with sleep bruxism